The Role of School Principals in Facilitating the Implementation of the Independent Learning Curriculum in Islamic Religious Education and Character Subjects at SDN Tenggilis 1 Mejoyo - Ulul Azmi Nur Rohmatulloh; Husniyatus Salamah Zainiyati; Hanun Asrohah; Iksan, Iksan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study examines the role of the principal in facilitating the implementation of the Independent Curriculum in Islamic Religious Education (PAI) at SDN Tenggilis Mejoyo 1 Surabaya. The Independent Curriculum is designed to provide students with the flexibility to choose learning activities that align with their interests and talents, employing a student-centered learning approach. The principal plays a vital role as an educator, manager, administrator, innovator, motivator, leader, and supervisor in supporting the curriculum's implementation. Through resource management, teacher training, and regular monitoring, the principal strives to create a conducive learning environment for the development of students' religious character. Despite challenges such as limited teacher understanding of the new curriculum and inadequate facilities, strategic measures are undertaken to ensure effective implementation. This study offers insights into the significance of the principal's role in supporting the successful implementation of the Independent Curriculum at the elementary school level.